Bande dessinée et art contemporain : La nouvelle scène de l'égalité : Arts: Le Havre 2010 : Biennale d'art contemporain - Morren, Linda; Berland, Alain; Bonnot, Léonard; Association de la biennale d'art contemporain du Havre, Le Havre; Morlot, Evelyne; Rives, Lucile; Sebag, Ari; Thévenet, Jean-Marc (Blou : Monografik éditions, 2010)
Alberola, Jean-Michel ; Atrabile ; Barré, Virginie ; Benchamma, Abdelkader ; Blanc, Christophe ; Bodé, Mark ; Bodé, Vaughn ; Bramati, Olivier ; Caron, Armelle ; Charlier, Jacques ; Devoye, Wim ; Deschamps, Gérard ; Evens, Brecht ; Echoesland ; Fondevila, Pauline ; Olislaeger, François ; Magazine, Frédéric ; Gerner, Jochen ; Hamon, John ; Hentgen, Hippolyte ; Kang, Seunghee ; Manouach, Ilan ; Pettibon, Raymond ; Pinard, Guillaume ; Plonk & Replonk ; Robbe, Hervé ; Ruiz, Francesc ; Ruppert & Mulot ; Scurti, Franck ; Soma Mashe, Jivya ; Swarte, Joost ; Touloub, Achraf ; Levaux, Aurélie William ; Winshluss
boek